A Comparison of Local Anesthetics for Intravenous Catheter Insertion in Hospitalized Pediatric Patients: A Randomized Clinical Pilot Trial. Issue 6 (November 2021) - Lozano, Sally; Sund, Grace; Guimera, Allison; Deukmedjian, Grace; Miller, Pamela S.
Abstract : Peripheral intravenous catheter (PIVC) insertion is one of the most painful procedures pediatric patients undergo during hospitalization. To date, local anesthetics delivered via cream, patch, and needle-free injection have not been rigorously evaluated together. This study aimed to investigate feasibility and potential efficacy of local anesthetics on pain intensity during PIVC insertion in an unblinded, single-center, randomized clinical pilot trial. Between March 2017 and February 2020, 88 hospitalized children aged 12 months to 18 years in an acute pediatric unit at an academic medical center were randomized to 1 of 3 local anesthetics: 1) lidocaine/prilocaine cream, 2) lidocaine/tetracaine patch, and 3) unbuffered lidocaine needle-free injection. Feasibility outcomes were recruitment and protocol adherence. Pain intensity was measured using the Face, Legs, Activity, Cry, Consolability (age <8 years) and Verbal Numeric Rating (VNRS) scales (age ≥8 years) before, during, and after procedure. Secondary outcomes included catheterization attempts, procedure time, and parent satisfaction. Recruitment rate was acceptable (2.7 patients per month). Protocol adherence was high (92%). Preliminary clinical findings showed no significant difference in pain intensity across treatments. Procedure time to successful insertion differed in the VNRS group, favoring unbuffered lidocaine needle-free injection. Conduct of a definitive, full-scale randomized clinical trial in the hospitalized pediatric population is feasible.